A study on moral values as reflected by two main characters in William Shakespeare’s Macbeth - Suatmo Pantja Putra (Universitas Merdeka Malang, 2019)
This study is concerned to find out the Elizabethan moral values which are described by Shakespeare in his play Macbeth. A deep analysis on the two main characters, Macbeth and Lady Macbeth, is done to explore their moral values seen from Christianity and the perspective of moral experts.This study applies approach which take account of three disciplines literature, religion and morality. The literary analysis helps to clarify the good and bad qualities of the two characters. The religious point is applied to explore the influence of Christian moral values, in relation to Elizabethan moral values, from which the Elizabethan people are Christians. Further, morality is used to revealed whether the balance of the two characters id, ego, and super ego also give influence to their downfalls.